Rancang Bangun Sistem Informasi Monitoring Data Performansi Mitra Speedy Berbasis Web Pada Pt.Telkom Regional Timur (Persero) - Ilhamsyah, Amirudin; Lusiani, Titik; Sutanto, Teguh (Jurnal JSIKA, 2012)
PT. Telekomunikasi Indonesia Tbk. East Regional to perform monitoring and continuous measurement of the performance of its partners to ensure achievement of established goals. Manager performance during this monitoring by requesting a report to the data center that handles the data speedy partners. Then the data center will conduct a search (query) data into a form to present a report to the manager. It is difficult for managers to monitor performance of the partners speedy sale. Because it takes a relatively long time. and lack of specific information can slow the speedy performance of partners in decision-making process because the people who are not managers can monitor the level of performance at any time. One solution to overcome these obstacles is by monitoring application performance speedy web-based partners. This application is intended for business performance manager” Keywords : Monitoring application, Performance, speedy,Query.